Epidemiology of Leptospira spp. infection in a beef cattle area of Argentina - Mariana Mazzanti; Mariana Mazzanti; Exequiel Scialfa; Exequiel Scialfa; Mariana Rivero; Mariana Rivero; Mariana Rivero; Juan Passucci; Juan Passucci (Frontiers in Veterinary Science, 2023)
Leptospirosis is an infectious disease caused by pathogenic Leptospira that affect humans and animals. This disease is complex and non-eradicable in nature. Therefore, the understanding of it is epidemiology in different environments is crucial to implement prevention and control measures. The prevalence of Leptospira infection in beef cattle farms is affected by multiple environmental, management and individual factors. In this study, a cross-sectional serological survey was carried on to estimate the prevalence of Leptospira antibodies in beef cattle in Tandil and Ayacucho Departments (Buenos Aires Province) and to identify risk factors and spatial clusters associated with seropositivity. Using a probabilistic two-stage sampling, 25 farms and 15 animals per farm were selected. The Microagglutination Test was used to analize all serum samples. Bivariate and multivariate analyses were performed. Seventy-three out of 375 cows were seropositive, representing a positivity rate of 19.47% (95% CI: 10.51–28.42), with Sejroe and Pomona being the most reactive serogroups: 9.33% (95% CI: 6.26–12.41) and 8.27% (95% CI: 5.35–11.19), respectively. The prevalence in Ayacucho was 23.11% (95% CI: 10.05–36.17), and in Tandil, 14% (95% CI: 3.25–24.75). The animals from Ayacucho presented 2.01 (1.16–3.49) more chances of being positive compared with those from Tandil (p < 0.01). After the Generalized Linear Mixed Model (GLMM) with random effect of farm-level risk, the presence of lagoons (OR: 7.32, 95% CI: 1.68–31.8, p < 0.05) and undulating terrain (OR: 0.24, 95% CI: 0.07–0.74, p < 0.05) were associated with bovine leptospirosis. Four spatial clusters with higher rates of seropositivity were detected. A new GLMM was performed with the significant variables detected in the first GLMM and a new variable, “being inside the spatial cluster,” being the only one that remained significant (OR: 9.58, 95% CI: 3.39–27.08, p < 0.0001). The animals inside the clusters belonged to farms with a greater presence of creeks (OR: 9.03, 95% CI: 3.37–24.18, p < 0.0001), higher accumulated rainfall (OR: 1.01, 95% CI: 1–1.01, p < 0.0001) and less undulating terrain (OR: 0.18, 95% CI: 0.10–0.35, p < 0.0001). We conclude that Leptospira is seroprevalent in beef cattle in Tandil and Ayacucho Departments, especially in the latter, where the largest cattle farms are located. Prevalence of seropositivity animals was associated with selected environmental risk factors.